Refuge in hell how Berlin's Jewish hospital outlasted the Nazis - Silver, Daniel B. (Houghton Mifflin Co., 2003)
Provides a close-up look at the story behind Berlin's Jewish Hospital, the only Jewish institution in Germany to survive the Holocaust, drawing on accounts of survivors to describe daily life in the hospital under the Nazis.